Case Report: Langerhans Cell Sarcoma With Intracranial and Extracranial Communication on the Left Frontal Bone - Xie, Shan; Shao, Zhilin; Shao, Dongqi; Du, Bang; Han, Yi; Li, Yu; Zhang, Binbin; Zheng, Xialin; Jiang, Zhiquan (Frontiers in Surgery, 2022)
Abstract Background: Langerhans cell sarcoma (LCS) is an extremely rare type of malignant tumor that originates from Langerhans cells (LC). It is characterized by the malignant proliferation and dissemination of LCs and is extremely invasive, with a rapid progression and poor prognosis. It can affect the liver, spleen, lymph nodes, and other tissues and organs of the body. The clinical manifestations are complex and diverse. The diagnosis of LCS is primarily based on the clinical manifestations, imaging examinations, laboratory examinations, and pathological examinations, among which pathological diagnosis is the gold standard. Treatment includes surgical resection of the lesions, radiotherapy and chemotherapy, immunotherapy, and hematopoietic stem cell transplantation. However, a unified and optimized treatment plan is currently lacking, and individualized treatment is generally accepted. Case presentation: In this study, we report an 18-year-old male patient with intracranial and extracranial communicative LCS that occurred in only the left forehead without metastasis to other regions, who had normal clinical hematological examination results. We adopted a treatment method of complete resection of the diseased tissue, which was pathologically examined following the operation. The pathological results showed CD1a (++), S-100 (++), CD68 (+), CyclinD1 (+), and Ki-67 (45%–50%), and with no recurrence or metastasis after long-term follow up. Conclusion: LCS is a rare clinically malignant tumor, and one that occurs in the intracranial and extracranial communication is even rarer. The diagnosis of LCS requires comprehensive consideration. Becase the prognosis of LCS is poor, an active adoption of an individualized treatment plan is crucial.